HUBUNGAN SISTEM INFORMASI AKUNTANSI DENGAN KINERJA USAHA KECIL DAN MENENGAH DI MALAYSIA - Tanjung, Amries Rusli; Agusti, Restu (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This research is intended to measure an influence between the implementation ofAccounting Information System (AIS) in Small and Medium Enterprises (SMEs) inMalaysia and effectiveness of performance in SMEs. All of this research is based ona survey conducted by empirical evidence that has been done in the Small andMedium Enterprises in select in Malaysia base on criteria in sample method.Moreover, to achieve the aims of this study, the framework or some hypothesis havedeveloped in accordance with previous research and literature review. Finding in thisresearch got the same result with previous researches that have positive relationsbetween the AIS and effectiveness performance of SMEs in Malaysia. For theconclusion, this research proved that SMEs has implemented AIS show a betterperformance, especially in the decision making process, internal control, and qualityof financial report. This Research has implications for Small and MediumEnterprises, literature, academic and non-academic and also for study in the future.Key work: Accounting Information System and Organization Performance